Peningkatan Penguasaan konsep fisika momentum dan impuls kelas X SMA dengan mengimplementasi model belajar 8E - Azhar; Wika Junilita; Dedi Irawan (Postgraduate, University of Mataram, 2023)
This research utilized the Physics at School application to utilize the Learning Cycle 8E model to explain students' conceptual mastery in class X SMA and identify any disparities in conceptual mastery for students in class X SMA. This kind of research uses a quantitative Nonequivalent Post-Test Control Group Design research design and a Quasi-Experimental research method. This research was performed at SMA Negeri 1 Teluk Kuantan. The aims of this research was to implement the Learning Cycle 8E model with assistance from the Physics at School program. In contrast, the second class uses conventional learning techniques as a control class. The data used in this research were concept mastery scores obtained from students who had learned physics using the Learning Cycle 8E model with assistance from the Physics at School program. Based on a descriptive and inferential examination of the data, it was found that the experimental class students' level of concept mastery increased by 73.08 points, while the control class was 69.70. Certainly, Learning Cycle 8E model, which is supported by the Physics at School application, has an impact on how well SMA Negeri 1 Teluk Kuantan children understand certain concepts.